2012
DOI: 10.1371/journal.pone.0050256
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in PNPLA3 and Risk of Non-Alcoholic Fatty Liver Disease in a Han Chinese Population

Abstract: We investigated the possible association between genetic variants in the Patatin like phospholipase-3 (PNPLA3) gene and nonalcoholic fatty liver disease (NAFLD) in a Han Chinese population. We evaluated twelve tagging single-nucleotide polymorphisms (tSNPs) of the PNPLA3 gene in a frequency matched case–control study from Fuzhou city of China (553 cases, 553 controls). In the multivariate logistic regression analysis, the rs738409 GG or GC, and rs139051 TT genotypes were found to be associated with increased r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 49 publications
3
38
3
Order By: Relevance
“…Other reports have examined the association between the PNPLA3 rs738409 C>G polymorphism and other forms of liver disease, most notably NAFLD, which leads to United States, Taiwan, China, Japan, or Malaysia (39)(40)(41)(42)(43). Indeed, in a Japanese study, Hotta et al ( 44 ) found that the risk of carrying the G allele was 0.44 in control patients and 0.60 in patients with NAFLD.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Other reports have examined the association between the PNPLA3 rs738409 C>G polymorphism and other forms of liver disease, most notably NAFLD, which leads to United States, Taiwan, China, Japan, or Malaysia (39)(40)(41)(42)(43). Indeed, in a Japanese study, Hotta et al ( 44 ) found that the risk of carrying the G allele was 0.44 in control patients and 0.60 in patients with NAFLD.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Two seminal population-based genome-wide association studies (GWAS) conducted in 2008 [137,138] identified a common non-synonymous single-nucleotide polymorphism in the patatin-like phospholipase domaincontaining protein 3 (PNPLA3) gene (rs738409 C > G; I148M), which encodes the multifunctional lipolytic enzyme adiponutrin (ADPN) [139] as a major determinant of inter-individual variation in hepatic fat content and plasma liver enzyme levels. The PNPLA3 rs738409 SNP has subsequently been reproducibly associated with increased susceptibility towards the onset and progression of NAFLD across boundaries for age, sex and ethnic background [139][140][141][142][143][144] . Findings from at least two recent meta-analyses have also confirmed the clinical relevance of PNPLA3 rs738409 as a potent genetic risk factor for NASH, severe hepatic fibrosis and hepatocellular carcinoma [145,146] .…”
Section: Incorporation Of Personalized Genomic Testing To Existing Comentioning
confidence: 99%
“…Polymorphisms of PNPLA3 gene have been found to be strongly associated with the pathogenic status of NAFLD in different populations [91][92][93] . PNPLA3 gene, encoding adiponutrin is known to have lipase activity in vitro and has been found to be involved in glucose and lipid metabolism [91] .…”
Section: Genes That Affect Lipolysismentioning
confidence: 99%